Identification of optimum working conditions in hydroelectric power plants for cavitation - Kahraman, Gokhan; Yucel, Halit Lutfi; Tasgin, Yahya (Pergamon-Elsevier Science Ltd, 2019)
Turbine faults in hydroelectric power plants not only reduce the operation time of the plant, but also cause a serious loss of income. One of the most important turbine faults is the turbine wheel wear caused by the cavitation and accordingly the other machine equipment faults which cause excessive vibration. In this study, cavitation intensity that the turbines have been exposed in operating conditions has been investigated. As a result of the calculations, optimum working conditions of the units have been determined with graphs obtained in various operating conditions. The obtained data can be easily applied to all hydroelectric power plants exposed to cavitation, and safe operating conditions can be determined.
Keywords: Cavitation; Hydroelectric power plant; Turbine wheel